Dignity of older people in a nursing home: Narratives of care providers - Jakobsen, Rita (Nursing ethics, 2010)
The purpose of this study was to illuminate the ethically difficult situations experienced by care providers working in a nursing home. Individual interviews using a narrative approach were conducted. A phenomenological-hermeneutic method developed for researching life experience was applied in the analysis. The findings showed that care providers experience ethical challenges in their everyday work. The informants in this study found the balance between the ideal, autonomy and dignity to be a daily problem. They defined the culture they work in as not supportive. They also thought they were not being seen and heard in situations where they disagree with the basic values of the organization. The results are discussed in terms of Habermas’s understanding of modern society. Care settings for elderly people obviously present ethical challenges, particularly in the case of those suffering from dementia. The care provider participants in this study expressed frustration and feelings of powerlessness. It is possible to understand their experiences in terms of Habermas’s theory of modern society and the concept of the system’s colonization of the life world.